Ativismo de acionistas no mercado acionário brasileiro : evidências e determinantes em empresas listadas na BM&FBovespa - Vargas, Luiz Henrique Fernandes (2013)
This study aims at verifying the characteristics and determinants of shareholder activism in public Brazilian companies. Shareholder activism means the attempt of shareholders to cause alterations in the company, without changing its control structure, as defined by Gillan e Starks (2007). The sample is made up of 322 companies for the year 2010 and 347 companies for 2012. The study analyzed minutes of the ordinary meetings, media news on activism, and complaints at the Brazilian Securities and Exchange Commission (CVM). In order to achieve our goals and show shareholder activism in the sample, an index made up of seven questions was employed, as well as logistic regression and multiple linear regression. The results show the existence of shareholder activism expressed in the minutes through proposals made before and during the meetings, opposing votes and refusal of proposals presented, as well as search for representation in board of directors and audit committee through the election effective members by minority shareholders. Evidence of shareholder activism was verified in news of that period, mainly incorporation events and capital closing operations. Because of the interest these events aroused in the media, the news about them were republished, which led to an increase in the figures from one year to another. As far as the proceedings filed at the Brazilian Securities and Exchange Commission are concerned, there was a decrease from 2010 to 2012, even though there was an increase in proceedings concerning “measures adopted by company’s administrator and/or controller". The Shareholder Activism Index showed the highest score for five of the seven questions for only two of the sample companies in the study period. The chances of a company to target of activism are negatively affected by return on equity and ownership concentration, and positively by firm size, board size , number of proposals during meetings and quantity of shareholders; both individuals and corporations. However, when using the variable “number of individual shareholders”, no statistical significance was found for the model referring to complaints filed at CVM. For companies that had been target of activism, multiple linear regression and activism measured by the index showed that the company is negatively affected by leverage, and positively affected by firm size and quantity of individual shareholders. Therefore, this study is a contribution the literature on shareholder activism in the Brazilian stock market by showing the existence of the former through methodology different from what had been used in international studies, i.e. analyzing three aspects: meeting minutes, media news, and complaints filed at Brazilian Securities and Exchange Commission. This variety of information allows verifying this phenomenon that is frequently analyzed in international studies, but scarcely investigated in the Brazilian market.